Investigation of olfactory function in a Panx1 knock out mouse model - Kurtenbach, Stefan; Whyte-Fagundes, Paige; Gelis, Lian; Kurtenbach, Sarah; Brazil, Émerson; Zoidl, Christiane; Hatt, Hanns; Shestopalov, Valery I.; Zoidl, Georg (Frontiers in Cellular Neuroscience, 2014)
Pannexin 1 (Panx1), the most extensively investigated member of a channel-forming protein family, is able to form pores conducting molecules up to 1.5 kDa, like ATP, upon activation. In the olfactory epithelium (OE), ATP modulates olfactory responsiveness and plays a role in proliferation and differentiation of olfactory sensory neurons (OSNs). This process continuously takes place in the OE, as neurons are replaced throughout the whole lifespan. The recent discovery of Panx1 expression in the OE raises the question whether Panx1 mediates ATP release responsible for modulating chemosensory function. In this study, we analyzed pannexin expression in the OE and a possible role of Panx1 in olfactory function using a Panx1−/− mouse line with a global ablation of Panx1. This mouse model has been previously used to investigate Panx1 functions in the retina and adult hippocampus. Here, qPCR, in-situ hybridization, and immunohistochemistry (IHC) demonstrated that Panx1 is expressed in axon bundles deriving from sensory neurons of the OE. The localization, distribution, and expression of major olfactory signal transduction proteins were not significantly altered in Panx1−/− mice. Further, functional analysis of Panx1−/− animals does not reveal any major impairment in odor perception, indicated by electroolfactogram (EOG) measurements and behavioral testing. However, ATP release evoked by potassium gluconate application was reduced in Panx1−/− mice. This result is consistent with previous reports on ATP release in isolated erythrocytes and spinal or lumbar cord preparations from Panx1−/− mice, suggesting that Panx1 is one of several alternative pathways to release ATP in the olfactory system.